The Survival Outcomes of Patients Requiring Prolonged Mechanical Ventilation - Chienhsiu Huang (Medicina, 2023)
Background and objectives: Patients who require prolonged mechanical ventilation typically experience poor long-term survival outcomes. However, there have been few studies conducted to investigate the five-year survival rate of these patients. This study aims to determine the factors that affect the five-year survival rate of patients who require prolonged mechanical ventilation, with the goal of improving their survival outcomes. Materials and Methods: The current retrospective, single-center study included all patients who required prolonged mechanical ventilation over a period of six years. We collected data on their age, sex, causes of acute respiratory failure leading to prolonged mechanical ventilation, comorbidities, receipt of a tracheostomy or not, weaning status, discharge conditions, and long-term outcomes. Results: The study examined the long-term outcomes of 403 patients who required prolonged mechanical ventilation until December 2018. Of the study population, 157 patients were successfully weaned from prolonged mechanical ventilation and discharged, 186 patients passed away in the hospital, and 60 patients remained ventilator-dependent. For all 403 patients receiving prolonged mechanical ventilation, the one-year and five-year survival rates were 24.3% and 14.6%, respectively. Among the 243 patients who were successfully weaned from prolonged mechanical ventilation, the corresponding rates were 32.6% and 21.0%. For the 157 discharged prolonged mechanical ventilation patients, the one-year and five-year survival rates were 50.3% and 32.6%, respectively. For the 60 ventilator-dependent patients, the one-year and five-year survival rates were 31.7% and 13.2%, respectively. The study revealed that successfully weaned from invasive mechanical ventilation and the receipt of a tracheostomy were influential factors in the five-year survival rate of patients requiring prolonged mechanical ventilation. Conclusions: Patients requiring prolonged mechanical ventilation may experience poor survival outcomes. Nevertheless, two key factors that can improve their long-term survival are successfully weaned from invasive mechanical ventilation and receipt of a tracheostomy.